Investigating Teacher Instructional Strategies in the Teaching of Natural Sciences in the Senior Phase - Netshivhumbe, Ndivhuwo Prudence (Studies in Learning and Teaching, 2025)
This paper examined the instructional strategies used by senior phase natural science teachers in schools located in the Vhembe District, Limpopo Province. The study employed a qualitative case study approach, with one natural science teacher from each of the three selected schools participating. Data were collected through semi-structured interviews and classroom observations. The findings of the study revealed that teachers employed a variety of teaching methods, explanatory frameworks, and activities as instructional strategies. These strategies facilitated interactions between learners and their teachers, as well as between learners and the subject matter. However, opportunities for learners to engage with one another were limited, as teachers primarily conveyed a significant amount of information to the class. Additionally, the study highlighted that the participating teachers did not have natural science as part of their formal teaching qualifications. Based on these findings, it is recommended that continuous development programs focus not only on subject matter knowledge but also on instructional strategies relevant to specific topics. Furthermore, the government should consider investing in the construction of laboratories and community libraries, as well as providing schools with qualified subject teachers and adequate teaching materials to support effective teaching and learning.